Avaliação técnica do trabalho desenvolvido no setor de acessibilidade, da assistência estudantil, da Universidade Federal do Triângulo Mineiro - estudo de caso - BATISTA, Diego de Morais (2018)
The present study is a final technical report, a result of research for the conclusion of the Master's Degree in Public Administration, at Universidade Federal do Triângulo Mineiro (UFTM). In this report, we analyzed, through the field, bibliographical and documental researches, the work developed at the UFTM Accessibility Area, as well as its difficulties and investment needs to optimize the services provided. Finally, interviews were conducted with four students attended by the sector, being one representative for each group, defined by: physical, sensorial - visual, sensorial - auditory and mental / learning disorders; a lecturer from each of these students; and two managers; in addition, we have considered the report analysis by Inclusive Tutors students. From the confirmation of the perceptions of the services provided, derived from interviews and reports, twenty-four perceptions were recorded that influenced thirteen important actions proposed to optimize the work of the Accessibility Area. It is important to highlight activities developed by the Area, especially the Inclusive Tutoring Program (ITP), as well as relevant reports regarding experiences and contact with students served by the ITP. It is understood that this work may and should influence new researches, besides being a reference for other educational institutions, especially the federal ones (FTI), in search of a better effectiveness of the actions developed for the accessibility of the disabled person in the student assistance Area.